Marguerite Yourcenar entre a pandemia e a alquimia - José Guimarães (Carnets)
The fascination with human spirituality guided Marguerite Yourcenar in the incessant search for the depths of the soul and in the desire for an asceticism that will allow man to rise to levels of knowledge and communion with the elements, inaccessible to those who lack self-reflexion. It is through alchemy, linked to the transcendent and the practice of medicine, connected to the human immanent that his hero Zénon gives a direct testimony, to the reader of L’Œuvre au Noir, of the painful, troubled and dangerous path that is the touchstone in the elevation of Humanity to a communion with the Universe. This journey made up of a mixture of transcendent and immanent is the object of this study.